Framework of contemporary media education system A study on non- media undergraduate students of West Bengal - Maitree Shee (IGNOU Journal of Media and Empowerment (ISSN: 3048-8478), 2025)
As a vital bridge between the world and its users, the media is expected to be reliable and easily understandable. Again, in this period of 'on-time news', there is a question of reliability regarding many news sources. Here comes the role of media literacy. The study explores the role of media education in equipping students with critical media literacy, ethical awareness, and practical skills essential for navigating the modern information landscape. Moreover, the study identifies the growing importance of media literacy, the need for standardised curricula and the role of industry-academia collaboration in enhancing media education. For assessing the students' approach towards introducing 'media studies' in their regular curriculum, as suggested by the New Education policy 2020, the research has used a mixed methods approach, combining survey analysis from selected students and interviews with experts. The findings highlight the gaps in the existing curriculum, revealing severed connections between academic institutions and industry demands.